Spiritual Personʼs Development in the Pedagogical Thought of National Emigration (the 1920s-1950s): Historioghraphical Analysis - Maryna Kubrakova (Pedagogical Discourse, 2013)
The article contains the historioghraphical review of the problem of spiritual personʼs development in the pedagogical thought of national emigration (the 1920s-1950s).The historioghraphical analysis of the problem of spiritual personʼs development in the pedagogical thought of national emigration (the 1920s-1950s)gives ground for identification of two stages: the first one is from 1919 to 1939, and the second – from 1945 to nowadays. The first stage is characterized by some different researches, which concerned the certain aspects of Ukrainian emigration, mainly, national, cultural and spiritual adaptation of Ukrainians abroad. And the second stage of studying the problem of spiritual personʼs development in the pedagogical thought of national emigration (the 1920s-1950s)has expanded both concerning its issues and the number of investigations. The article shows that the problem of study of spiritual personʼs development in the pedagogical thought had the following directions: spiritual, religious and unreligious ones.